Transdentinal cytotoxicity of experimental adhesive systems of different hydrophilicity applied to ethanol-saturated dentin - Bianchi, Luciana [UNESP]; Ribeiro, Ana Paula Dias; De Oliveira Carrilho, Marcela Rocha; Pashley, David H.; De Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (Elsevier, 2013)
The aim of this study was to evaluate the transdentinal cytotoxicity of experimental adhesive systems (EASs) with different hydrophilicity and dentin saturation solutions on odontoblast-like cells. One hundred 0.4-mm-thick dentin discs were mounted in in vitro pulp chambers and assigned to 10 groups. MDPC-23 cells were seeded onto the pulpal side of the discs, incubated for 48 h. The EASs with increasing hydrophilicity (R1, R2, R3 and R4) were applied to the occlusal side after etching and saturation of etched dentin with water or ethanol. R0 (no adhesive) served as controls. R1 is a non-solvated hydrophobic blend, R2 is similar to a simplified etch-and-rinse adhesive system and R3 and R4 are similar to self-etching adhesives. After 24 h, cell metabolism was evaluated by MTT assay (n = 8 discs) and cell morphology was examined by SEM (n = 2 discs). Type of cell death was identified by flow cytometry and the degree of monomer conversion (%DC) was determined by infrared spectroscopy (FTIR) after 10 s or 20 s of photoactivation. Data were analyzed by the Kruskal-Wallis and Mann-Whitney tests (α = 0.05). Dentin saturation with ethanol resulted in higher necrotic cell death ratios for R2, R3 and R4 compared with water saturation, although R2 and R3 induced higher SDH production. Photoactivation for 20 s significantly improved the %DC of all EASs compared with 10 s. A significant positive correlation was observed between the degree of hydrophilicity and %DC. In conclusion, except for R1, dentin saturation with ethanol increased the cytotoxicity of EASs, as expressed by the induction of necrotic cell death. © 2013 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Adhesive systems; Cytotoxicity; Dentin; Ethanol; Odontoblast-like cells; Monomer conversions; Necrotic cell deaths; Photo activations; Positive correlations; Self-etching adhesives; Water saturations; Cell death; Etching; Hydrophilicity; Infrared spectroscopy